Triangular Srr Based Triple Band Amc Backed Antenna for High Gain Sub6ghz Application (International Journal of Innovative Research in Engineering & Management, 2022)
This article describes a triple band  monopole antenna. t has been assumed that the WiMAX  band application is objective. In order to attain the required  band, various iterations of the proposed antenna design are  carried out. The proposed antenna in the shape of broken  hearts operates in the frequency range of 3.2GHz to  4.1GHz. In the final iteration, the heart-shaped double  slotted ring resonator (SRR) with two different radii is seen  to improve the bandwidth (900MHz) and gain (3dB). In  this design, additional parameters like VSWR  (approximately 2 at the WiMAX band), impedance (real  and imaginary), and efficiency (approximately 89%) have  been observed. As a result, the proposed monopole antenna  in the shape of a broken heart that operates in the WiMAX  band exhibits high efficiency, reduced size, and moderate  gain. which play a crucial role in the WIMAX application  band.
Keywords: Triple Band Antenna; Wimax; Slotted Ring Resonator (Srr); Vswr